Diary of an awesome friendly kid - Kinney, Jeff (New York : Amulet Books, 2019)
In his first journal, middle schooler Rowley Jefferson, Greg Heffley's sidekick, records his experiences and misguided decision to write a biography of Greg, who, in his own mind, is destined to become rich and famous.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Authorship -- Fiction; Biography -- Fiction; Diaries -- Fiction; Humorous stories; JUVENILE FICTION / General; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / General